ECOLOGICAL STATE OF THE MARINE EDGE OF THE KILIA DANUBE DELTA IN 2011–2012 - ALEKSANDR CHEROY; OLEG DYAKOV; ELENA ZHMUD; VERONIKA PRYKHODKO (Revue Roumaine de Géographie)
The results of observations of the dynamics of the marine edge of the Danube Delta in 2011–2012 describe the main trends in the individual sections, taking into account the factors of their formation. Also, the results of observations of littering the sea edge of the Danube Delta with plastic waste, the registration of the dead dolphins, as well as botanical research are reported herein.